Clinical characteristics of generalized anxiety disorder: older vs. young adults. (17th February 2018) - Altunoz, Umut; Kokurcan, Ahmet; Kirici, Sevinc; Bastug, Gulbahar; Ozel-Kizil, Erguvan Tugba
Abstract: Background: Generalized anxiety disorder (GAD) is one of the most common anxiety disorders in older people. Although GAD in older adults seems to differ in many aspects like clinical presentation, severity and treatment response, there is a paucity of comparative research. Aims: The aim of the study is to compare the clinical presentation of GAD between older and young adults. Methods: One hundred and two non-demented older patients (age ≥65) and 64 young patients (age <45) who were diagnosed with GAD according to the DSM-IV-TR criteria were included to the study. Socio-demographic Data Form, the Structured Clinical Interview for DSM Disorders-1 (SCID-1), the Questionnaire for the Suggested Behavioral Criteria of GAD for DSM-5, the Hamilton Depression Scale (HAM-D), the Generalized Anxiety Disorder Severity Scale (GADSS) and the Sheehan Disability Scale (SDS) were applied to both groups. Results and conclusions: Older GAD patients had more disturbances of sleep, less reassurance seeking behaviors, higher rates of depression and higher depression severity when compared to the young patients. Although older people seemed to have a lower severity of GAD, they had higher disability due to worries. Older patients worried more about their own health and family well-being, whereas young patients worried more about future and other's health.